2008
DOI: 10.29302/oeconomica.2008.10.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Overconfidence And Trading Volume: Evidence From An Emergent Market

Abstract: It has been a challenge for financial economists to explain some stylized facts observed in securities markets, among them, high levels of trading volume. The most prominent explanation of excess volume is overconfidence. High market returns make investors overconfident and as a consequence, these investors trade more subsequently and make some transactions more aggressively. The aim of our paper is to study the impact of the phenomenon of overconfidence on the trading volume and its role in the formation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
1
8
1
Order By: Relevance
“…The studies conducted by Gervais and Odean (2001), Statman et al (2007), Chuang and Lee (2006), Korkmaz and Çelik (2007), Zaiane and Abaoub (2009), Otluoğlu ( 2009), Horasan and Bozkurt ( 2016) and Alsabban and Alarfaj (2020), who found that overconfidence and selfattribution increase the trading volume, support the same finding reached as a result of this study. In addition, Boyacıoğlu et al (2010) and Gaygusuz (2008)'s finding that volatility is the Granger cause of trading volume contradicts the result of this study.…”
Section: Discussionsupporting
confidence: 87%
“…The studies conducted by Gervais and Odean (2001), Statman et al (2007), Chuang and Lee (2006), Korkmaz and Çelik (2007), Zaiane and Abaoub (2009), Otluoğlu ( 2009), Horasan and Bozkurt ( 2016) and Alsabban and Alarfaj (2020), who found that overconfidence and selfattribution increase the trading volume, support the same finding reached as a result of this study. In addition, Boyacıoğlu et al (2010) and Gaygusuz (2008)'s finding that volatility is the Granger cause of trading volume contradicts the result of this study.…”
Section: Discussionsupporting
confidence: 87%
“…Many studies investigate the investors’ overconfidence in Tunisian stock market (Zaiane and Abaoub, 2009, 2010; Naoui and Khaled, 2010; Dhaoui, 2011). Empirical findings point out that trading volume increases after a series of high returns announcements, which confirms that Tunisian investors are overconfident.…”
Section: Survey Of the Literaturementioning
confidence: 99%
“…Whilst Griffin et al (2007) observe 46 different stock markets and find strong evidence of investor overconfidence, studies by Zia et al (2017) and Alsabban and Alarfaj (2020) also find evidence of overconfidence on the Pakistani and Saudi equity markets, respectively. On the contrary, Zaiane and Abaoub (2009) find weak evidence of investor overconfidence in the Tunisian stock market. Overall, Chuang and Lee (2006), Abbes (2013), andJlassi et al (2014) report that trading volume induced by overconfident trading is positively related to market volatility.…”
Section: Empirical Evidence Of Investor Overconfidencementioning
confidence: 72%
“…Other evaluations of the equity market have overwhelmingly found evidence of the overconfidence bias 1 affecting investment decisions (Baker et al, 2019;Jlassi et al, 2014;Meier & de Mello, 2020;Zaiane & Abaoub, 2009). The presence of investor overconfidence has been examined for markets of different asset classes, including stocks (Gupta et al, 2018), commodities (Yung & Liu, 2009), real estate (Lin et al, 2010) and index funds (Bailey et al, 2011).…”
Section: Public Interest Statementmentioning
confidence: 99%